Prospective observational study on the accuracy of predictors of high-grade atrioventricular conduction block after transcatheter aortic valve implantation (CONDUCT-TAVI): study protocol, background and significance. Issue 3 (8th March 2023) - Rao, Karan; Bhatia, Kunwardeep; Chan, Bernard; Cowan, Mitchell; Saad, Natasha; Baer, Alexandra; Sritharan, Hari; Bromhead, Ingrid; Whalley, David; Allahwala, Usaid K; Hansen, Peter; Bhindi, Ravinay
Abstract : Introduction: Aortic stenosis is the most common cardiac valve pathology worldwide and has a mortality rate of over 50% at 5 years if left untreated. Transcatheter aortic valve implantation (TAVI) is a minimally invasive and highly effective alternative treatment option to open-heart surgery. High-grade atrioventricular conduction block (HGAVB) is one of the most common complications after TAVI and requires a permanent pacemaker. Due to this, patients are typically monitored for 48 hours post TAVI, however up to 40% of HGAVB may delayed, and occur after discharge. Delayed HGAVB can cause syncope or sudden unexplained cardiac death in a vulnerable population, and no accurate methods currently exist to identify patients at risk. Methods and analysis: The prospective observational study on the accuracy of predictors of high-grade atrioventricular conduction block after transcatheter aortic valve implantation (CONDUCT-TAVI) trial is an Australian-led, multicentre, prospective observational study, aiming to improve the prediction of HGAVB, after TAVI. The primary objective of the trial is to assess whether published and novel invasive electrophysiology predictors performed immediately before and after TAVI can help predict HGAVB after TAVI. The secondary objective aims to further evaluate the accuracy of previously published predictors of HGAVB after TAVI, including CT measurements, 12-lead ECG, valve characteristics, percentage oversizing and implantation depth. Follow-up will be for 2 years, and detailed continuous heart rhythm monitoring will be obtained by inserting an implantable loop recorder in all participants. Ethics and dissemination: Ethics approval has been obtained for the two participating centres. Results of the study will be submitted for publication in a peer-reviewed journal. Trial registration number: ACTRN12621001700820.